2014
DOI: 10.1007/s11055-014-9999-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of EEG Theta and Gamma Rhythms in Normal Children and Children with Early Childhood Autism

Abstract: Previous studies [7,8] have addressed the question of the extent to which EEG characteristics typical of adult schizophrenia patients apply to children with early childhood autism (ECA). It has become possible to state the problem in these terms since clinical studies of ECA demonstrated that positive symptoms could arise and that ECA could develop into a processual disorder of the schizophrenia type [1]. Many children with ECA are diagnosed with "schizophrenia" at age 7-8 years. We were interested to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…van Diessen et al confirms the increase in gamma power, particularly in the frontal, parietal, and temporal regions in the relaxed eyes open condition ( 53 ). Stroganova et al replicate this finding, using a visual attention task ( 59 ), while Lushchekina et al supports these findings in two studies involving a cognitive task ( 64 ).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…van Diessen et al confirms the increase in gamma power, particularly in the frontal, parietal, and temporal regions in the relaxed eyes open condition ( 53 ). Stroganova et al replicate this finding, using a visual attention task ( 59 ), while Lushchekina et al supports these findings in two studies involving a cognitive task ( 64 ).…”
Section: Resultsmentioning
confidence: 83%
“…While Daoust et al, Tani et al, Elhabashy et al, and Yang et al show increased power in the theta band in two studies performed during sleep, one during a relaxed eyes open and one involving a cognitive task (52, 60, 61, 65); three studies show a reduction in theta power in relaxed eyes open conditions and during a cognitive task (55, 56, 64). Variations in the participants’ age, as well as small sample sizes might lead to the lack of consistency in these results.…”
Section: Resultsmentioning
confidence: 95%
“…Student's t-test was used to obtain the important differences for intragroup comparisons. It was reported that the spectral power of the theta rhythm was lower in autistic children than in healthy children, whereas the gamma power was larger [51].…”
Section: Discussionmentioning
confidence: 92%
“…To the best of our knowledge, no previous research reports differences in theta power during NREM sleep in populations with ASD. Research findings in the wake state in children (5–7 years) with ASD show decreased spectral power and mean coherence in theta in left and right occipital regions during rest and a counting task compared to controls (Kozhushko, ; Lushchekina, Podreznaya, Lushchekin, Novototskii‐Vlasov, & Strelets, ). Importantly, a clear theta peak during NREM sleep seems to disappear with increasing age (Kurth et al, ), and therefore, differences in theta frequencies may not be captured when comparing older age groups (adults).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the present pilot study where we identified increased beta power in the spectral features of the EEG. It has been hypothesized that excessive higher frequency oscillations such as beta and gamma (Lushchekina et al, ; Orekhova et al, ) point to imbalances in synaptic excitation and inhibition in the cortex (Orekhova et al, ). For example, Orekhova et al () found increased gamma and beta oscillatory power during wakefulness EEG under sustained visual attention (e.g., bubbles are blown by the experimenter) in ASD.…”
Section: Discussionmentioning
confidence: 99%